Bibliometric Analysis of Self-Confidence in Sports Activities Based on Scopus-Indexed Scientific Articles (2010–2024) - Mayasari, Elisa; Kusnaedi; Hidayat, Yusuf (Universitas PGRI Palembang, 2025)
This study aims to map to analyze the development of research and find future research ideas related to the study of sports psychology and self-confidence in sports in students of the master's program in sports using bibliometric analysis methods. The sampling technique used was a total sampling of 413 article titles from the 2014 to May 2024 publication year which was selected from 413 titles obtained from the Scopus page. Samples were collected using the Comma Separated Value (CSV) format. This research was conducted using a bibliometric analysis method using the VOSviewer application. From 413 titles, 162 keywords were obtained with a minimum of 5 occurrence criteria and produced 8 mapping clusters. The mapping results show that self-confidence is a topic of articles that is quite often used in journals and articles. The results of the analysis recommend ideas for future research such as self-confidence studies in sports in athletes, the general public, students, students to the elderly or the development of fields related to sports in athletes in various phases of training, try out to the level of matches at the regional and international levels.